Made in the Womb: Maternal Programming of Offspring Cardiovascular Function by an Obesogenic Womb - Diniz, Mariana S. (2023)
Obesity incidence has been increasing at an alarming rate, especially in women of reproductive age. It is estimated that 50% of pregnancies occur in overweight or obese women. It has been described that maternal obesity (MO) predisposes the offspring to an increased risk of developing many chronic diseases in an early stage of life, including obesity, type 2 diabetes, and cardiovascular disease (CVD). CVD is the main cause of death worldwide among men and women, and it is manifested in a sex-divergent way. Maternal nutrition and MO during gestation could prompt CVD development in the offspring through adaptations of the offspring's cardiovascular system in the womb, including cardiac epigenetic and persistent metabolic programming of signaling pathways and modulation of mitochondrial metabolic function. Currently, despite diet supplementation, effective therapeutical solutions to prevent the deleterious cardiac offspring function programming by an obesogenic womb are lacking. In this review, we discuss the mechanisms by which an obesogenic intrauterine environment could program the offspring's cardiovascular metabolism in a sex-divergent way, with a special focus on cardiac mitochondrial function, and debate possible strategies to implement during MO pregnancy that could ameliorate, revert, or even prevent deleterious effects of MO on the offspring's cardiovascular system. The impact of maternal physical exercise during an obesogenic pregnancy, nutritional interventions, and supplementation on offspring's cardiac metabolism are discussed, highlighting changes that may be favorable to MO offspring's cardiovascular health, which might result in the attenuation or even prevention of the development of CVD in MO offspring. The objectives of this manuscript are to comprehensively examine the various aspects of MO during pregnancy and explore the underlying mechanisms that contribute to an increased CVD risk in the offspring. We review the current literature on MO and its impact on the offspring's cardiometabolic health. Furthermore, we discuss the potential long-term consequences for the offspring. Understanding the multifaceted effects of MO on the offspring's health is crucial for healthcare providers, researchers, and policymakers to develop effective strategies for prevention and intervention to improve care.